If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 = 6x + -6 Reorder the terms: 6 + 2x = 6x + -6 Reorder the terms: 6 + 2x = -6 + 6x Solving 6 + 2x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 6 + 2x + -6x = -6 + 6x + -6x Combine like terms: 2x + -6x = -4x 6 + -4x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 6 + -4x = -6 + 0 6 + -4x = -6 Add '-6' to each side of the equation. 6 + -6 + -4x = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = -6 + -6 -4x = -6 + -6 Combine like terms: -6 + -6 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| ac+ax=b+6 | | 3=-6n+7n+18 | | 3d-14+6d+9= | | u^2=100 | | 3[a-5]=-6 | | 14+8x=-4+2x | | 4y-7+y+51=6y+50-4y | | x-1+6x=20 | | 3x+4y-7x-7y= | | 3m+(m+1)=6m+1 | | 3e(3e-10)=2 | | 9x(x+2y+3z)= | | 6s^3+23s^2+33s=13s | | 3x-5=5+3x | | y+x^2-2x=0 | | x+y^2-2y=0 | | 10y+5x=100 | | 4y-24-9y+31= | | -4(y-3)=6y-38 | | f(-2)=-2+2(-2-1) | | -9x+-18+25=-38 | | 3+(-22)= | | 7-11x=x-33 | | 3log(7)(4)-5log(7)(m)= | | f(3)=3+2(3-1) | | -2x-10=44+8x | | 5t-2t=t | | 2z^2+7x=0 | | -4(2-y)+3y=4(y-4) | | (2x+4)(x-3)=0 | | f(-2)=-3(4-2)+2 | | 2x-3=4y+6 |